The Local Inflammatory Profile and Predictors of Treatment Success in Subarachnoid Neurocysticercosis. (3rd December 2020) - Harrison, Sarah; Thumm, Lauren; Nash, Theodore E; Nutman, Thomas B; O'Connell, Elise M
Abstract: Background: Subarachnoid neurocysticercosis (SANCC) represents the most severe and difficult to treat form of neurocysticercosis. The inflammatory response contributes significantly to the morbidity and mortality of the disease. This study sought to understand the nature and evolution of the inflammation associated with SANCC, and evaluate for predictors of time to cure. Methods: There were 16 subjects with SANCC (basilar cistern, sylvian fissure, and/or spinal involvement) during active infection who had cerebrospinal fluid (CSF) cytokine and chemokine profiling, of whom 9 had a second CSF sample at (or following) the time of cure. The relationships between clinical parameters and cytokine/chemokine results were assessed. Results: Compared to pools of healthy donor CSF, those with active SANCC showed a significant ( P < .05) increase in chemokines and cytokines associated with Type 1 immunity (interferon [IFN] γ, interleukin [IL] 12p70, C-X-C Motif Ligand 10 CXCL-10); Type 2 immunity (IL-10, IL-13); IFNα2; and the chemokines Macrophage inflammatory protein MIP-1α/CCL3, MIP-1ß/CCL4, and Vascular Endothelial Growth Factor VEGF that appears to be locally (central nervous system [CNS]) produced. Compared to those with active disease, those with CSF taken at the time of cure showed a significant decrease in most of these chemokines and cytokines. Despite this, CSF from cured SANCC patients had levels of IL-10 ( P = .039), CXCL-10 ( P = .039), and IL-12p70 ( P = .044) above those seen in CSF from uninfected subjects. High ratios of IL-12p70/IL-10 early in infections were associated with a shorter time to cure (r = −0.559; P = .027), and a high Taenia solium burden (by quantitative polymerase chain reaction) was associated with longer times to cure (r = 0.84; P = .003). Conclusions: SANCC is associated with a marked, CNS-localized cytokine-/chemokine-driven inflammatory response that largely decreases with curative therapy, though some analytes persisted above the normal range. The relative balance between proinflammatory and regulatory cytokines may be an important determinant for a cure in SANCC. Abstract : Cerebrospinal fluid cytokine and chemokine elevations in subjects with subarachnoid neurocysticercosis (SANCC) early in treatment and changes that occur following cure are correlated with clinical parameters. The balance of Type 1/regulatory cytokines may be important in achieving cure in SANCC.